In Vitro Screening Ketahanan Galur Padi (Oryza Sativa) B7 Hasil Rakitan Politeknik Negeri Lampung Terhadap Keracunan Besi (Fe) - onny Chrisna Pandu Pradana; Siti Novridha Andini (Politeknik Negeri Lampung., 2019)
This research aimed to invstigate the response of paddy culture (B7 strain) assembled by Lampung State Polytechnic to the iron toxicity tolerance. The research was done at Plant Tissue Culture Laboratory, Lampung State Polytechnic, from July to September 2019. Treatments were single arranged in a completely randomized design with three replications. The treatment tried was five levels of Fe concentrations (5,6 ppm 28 ppm, 56 ppm, 84 ppm, 112 ppm, and control). Each replication consisted of three culture bottle containing one explant. The homogenity of data was tested using Barlett test. If the assumption were fulfilled then analysis of variance is executed using STATISTIX 10, and then followed by the Honest Significant Difference (HSD) test in 5% alpha for mean separation and RPA analysis. The result of this research showed that the B7 strain has tolerance to iron toxicity until 56 ppm of Fe concentration, it can be concluded from the PAR value of its strain (>0,50). Meanwhile inÂ 84 and 112 ppm of Fe concentration, the RPA value of B7 starin (<0,50), and it is indicate that its strain is sensitive.Â